Danish Arctic Expeditions, 1605 to 1620, Volume 1, The Danish Expeditions to Greenland in 1605, 1606, and 1607 In Two Books - Gosch, Christian Carl August 1832-1913 (Cambridge University Press, 1897)
The publications of the Hakluyt Society (founded in 1846) made available edited (and sometimes translated) early accounts of exploration. The first series, which ran from 1847 to 1899, consists of 100 books containing published or previously unpublished works by authors from Christopher Columbus to Sir Francis Drake, and covering voyages to the New World, to China and Japan, to Russia and to Africa and India. This 1897 volume contains accounts of early seventeenth-century expeditions to Greenland, two Danish (but piloted by the Englishman John Hall), and one led by Hall himself, with William Baffin as pilot. This is the first publication of Hall's report to the Danish king, illustrated with four maps from the 1605 expedition, which had only recently been rediscovered. The object of the expeditions was to re-establish communication with, and commercial exploitation of, what had formerly been a fertile region colonised by the Danes
Title from publisher's bibliographic system (viewed on 05 Oct 2015)